Gender inequalities in Portuguese gymnasts between 2012 and 2016 - Silva, M.-R. G.; Santos-Rocha, R.; Barata, P.; Saavedra, F. (Science of Gymnastics Journal, 2017)
Gender participation rates are different and the potential reasons are namely sports availability and stereotypes. In spite of gymnastics being recently considered as an "early specialization" sport, characterized by a higher number of female participants than male ones, it has been highlighted that there are much less published studies in female athletes than in males. The aim of this study was to analyze the gender participation among Portuguese gymnasts according to gymnastics` disciplines. An individual authorized database of all national gymnasts involved in the National School of Gymnastics of the Gymnastics Federation of Portugal among four athletic seasons, namely 2012/2013,2013/2014, 2014/2015 and 2015/2016 was used. From a sample of 14,742 gymnasts, 81.3% were female and only 18.7% were male during the athletic season of 2012/2013. Similar results were found in the next three seasons as follows: 83.3% females and 16.7% males in 2013/2014, 84.9% females and 15.1% males in 2014/2015 and 85.3% females and 14.7% males in 2015/2016. Significantly gymnasts-gender differences were observed for all disciplines. No differences between genders were observed in Rhythmic Gymnastics, Women's Artistic Gymnastics and Men's Artistic Gymnastics due to the exclusive sport participation of female and male gymnasts, respectively. Gymnastics should improve participation and combat gender inequalities.